Age at epilepsy onset in patients with focal cortical dysplasias, gangliogliomas and dysembryoplastic neuroepithelial tumours. (May 2018) - Rácz, Attila; Müller, Andreas-Markus; Schwerdt, Johannes; Becker, Albert; Vatter, Hartmut; Elger, Christian E.
Highlights: Age at epilepsy onset was investigated in patients with FCDs and neuroglial tumours. The spectrum of age at epilepsy onset is very broad in both patient groups. FCDs cause epilepsy earlier than neuroglial tumours. Positive family history for epileptic seizures is more frequent in FCD-patients. Abstract: Purpose: The age at epilepsy onset in patients with inborn or very early acquired brain lesions depends on the epileptogenic potential of the lesion and the patients' individual "susceptibility" to epileptic seizures. To gain insight into these determinants, we analysed the case history of patients with focal cortical dysplasias (FCDs) and neuroglial tumours. Methods: In a systematic, retrospective analysis comprised of 233 patients who underwent surgery (116 with FCDs and 117 with neuroglial tumours), we evaluated the age at epilepsy onset according to histopathologic subgroups, lesion location and family history. Results: Epilepsy onset was significantly earlier in patients with FCD than for those with neuroglial tumours (FCDs: 8.06 ± 0.74 years, gangliogliomas: 15.86 ± 1.24 years, dysembryoplastic neuroepithelial tumours (DNTs): 19.18 ± 2.47 years; p < 0.00001). FCDs were most frequently located in the frontal, whereas neuroglial tumours most frequently in the temporal lobe. For FCD patients, the age at epilepsy onset was not dependent on lesion location, whereas DNTs in a temporal location were associated with a later epilepsy onset than gangliogliomas and extratemporal DNTs. A positive family history for epilepsy or epileptic seizures was found more frequently among patients with FCDs (FCDs: 20.4%, neuroglial tumours: 8.1%; p = 0.013). Conclusion: We postulate that the age difference at epilepsy onset between patients with FCDs and neuroglial tumours can be attributed – at least partially – to unidentified genetic factors underlying the epileptogenic potential of the brain tissue. Additionally, the large variance in the age at epilepsy onset is possibly also genetically determined.